Influence of tarâchar interaction on solid fuel formation by co-pyrolysis of bamboo and waste plastic - Sasaki, Y. (2022)
Co-pyrolysis of bamboo and plastic powder was conducted in order to investigate how to produce âecologicalâ solid fuel. The mixing percentage of the powders wp and the setting temperature of the reactor wall TS were changed. At TSÂ =Â 573 K the decomposition of the simulated waste plastic was progressed on the surface of the bamboo char during co-pyrolysis while the tar from bamboo pyrolysis was wrapped by the molten plastic. The pores on the surface of the bamboo particles decreased with wp because they could be wrapped by the molten plastic. The particle size increased with wp. On the other hand, at TSÂ =Â 673 K the co-pyrolysis of bamboo and simulated waste plastic was disturbed partly by the interaction during co-pyrolysis of polypropylene (PS) and Polyethylene terephthalate while the co-pyrolysis of bamboo and PS was progressed. The grindability increased with TS and decreased with wp as most of the molten plastic coagulated after co-pyrolysis because the shape of particles changed from small fibrous particles to large granular particles with wp. At 30 wt < wp < 70 wt, the higher heating value (HHV) at TSÂ =Â 673 K was mostly lower than that at TSÂ =Â 573 K because the char yield in the mixture was lower than that of the expected char yield due to the progress of the simulated waste plastic pyrolysis at TSÂ =Â 673 K. The energy yield had a local minimum value at wpÂ =Â 10Â wt because the char yield increased by the coating of molten plastic during co-pyrolysis even if the TS increased. The energy yield decreased with TS. The optimum condition for the solid fuel, which was evaluated by grindability, HHV, and energy yield was TSÂ =Â 623 K and wpÂ =Â 10Â wt. Â© 2022 American Institute of Chemical Engineers.